CanCore: Metadata for Learning Objects - Norm Friesen; Anthony Roberts; Sue Fisher (Canadian Journal of Learning and Technology, 2002)
The vision of reusable digital learning resources or objects, made accessible through coordinated repository architectures and metadata technologies, has gained considerable attention within distance education and training communities. However, the pivotal role of metadata in this vision raises important and longstanding issues about classification, description and meaning. The purpose of this paper is to provide an overview of this vision, focusing specifically on issues of semantics. It will describe the CanCore Learning Object Metadata Application Profile as an important first step in addressing these issues in the context of the discovery, reuse and management of learning resources or objects.